Smart proximity based service agents on mobile handsets - Lim, Luo Ren (2013)
The availability of high performance smartphones had generated much interest in services that integrates computing capabilities into daily life. Research in this area focuses on making consumer devices context aware and appropriate to the circumstances. This thesis describes the development of an application distribution manager for non-persistent mobile application. We looked at different aspects of localization technologies available today and how these techniques are implemented in positioning systems. There is a gap in research on mobile service application distribution using location as the context. The thesis considers context modelling as a tool for improving ubiquitous computing. Context modelling is an important aspect in localization as it dictates the flow of information input into a system and the corresponding information outflow. Such a modelling tool can help develop a structured approach to handle location information. We describe a context refinement scheme that helps to manage context information while supporting user autonomy and control. We list the practical consideration on how the context refinement scheme can be applied to mobile localization based on the environment in which it operates. We looked at challenges associated with mobile environment and the proposals to mitigate such problems. Signal drag is a key issue identified to be resolved for the implementation of a proximity based mobile distribution service. A marked improvement in reducing signal drag in a wireless medium is observed using a proposed cluster based approach. The proposed cluster based solution is more efficient in identifying the relative contributions from wireless data. It is incorporated into the localization aspect of the proposed proximity distribution mechanism. The system is capable of distributing relevant service applications when in proximity to a smart space The prototype proximity based software distribution platform tags applications to smart service areas. Smart spaces are predefined areas that provide related service applications in the vicinity. This application distribution framework achieved context awareness by pushing only relevant applications to users when they are in a service area. The software prototype was tested in a real world setting using windows based and android based platforms and the results showed good recognition rate for areas of interest based on user’s context and interest.